2018
DOI: 10.7717/peerj.4476
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PCV2e strains in Southeast China

Abstract: Porcine circovirus 2 (PCV2) has been prevalent in swine herds in China since 2002, causing severe economic loss to the pig industry. The number of live pigs in southeast China is > 20 million. Since information on the genetic variation of PCV2 in the Fujian province is limited, the objective of the present work was to investigate the epidemiological and evolutionary characteristics of PCV2 in southeast China from 2013 to 2017. Of the 685 samples collected from 90 different swine herds from 2013 to 2017, 356 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
0
37
1
Order By: Relevance
“…Notably, recombination is very important for viral evolution and may modify the virulence and pathogenicity of PCV2. Inter‐genotypic and intragenotypic recombination between PCV2 has been reported in both in vitro studies and field conditions (Cai et al, ; Franzo, Cortey, Segalés, Hughes, & Drigo, ; Guo et al, ; Jiang et al, ; Liu et al, ; Liu, Wang, Zhu, Sun, & Wu, ; Wang et al, ). Notably, recombination events between PCV1 and PCV2 have also been detected (Gagnon, Music, Fontaine, Tremblay, & Harel, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, recombination is very important for viral evolution and may modify the virulence and pathogenicity of PCV2. Inter‐genotypic and intragenotypic recombination between PCV2 has been reported in both in vitro studies and field conditions (Cai et al, ; Franzo, Cortey, Segalés, Hughes, & Drigo, ; Guo et al, ; Jiang et al, ; Liu et al, ; Liu, Wang, Zhu, Sun, & Wu, ; Wang et al, ). Notably, recombination events between PCV1 and PCV2 have also been detected (Gagnon, Music, Fontaine, Tremblay, & Harel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have revealed that PCV2a, PCV2b, PCV2d and PCV2e exist in China. In the past few years, PCV2b and PCV2d have been the predominant genotypes identified in Chinese swine herds (Cai et al, ; Guo et al, ; Jiang et al, ; Liu et al, ; Wang et al, ). Furthermore, different genotypes or different groups within the same genotype of PCV2 may coexist in the same swine herd in China, which may facilitate virus recombination (Cheung, ; Zhai et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCV2e is a new genotype that has been circulating in the USA since 2015, the ORF2 sequences of which have 12 or 15 additional nts (CTT/TCTTA-TATGTAA) compared to those of PCV2a-PCV2d. PCV2e was reported in China for the first time in 2017 [14,15]. Intermediate and new genotypes have been proposed, with increasing numbers of sequences available in recent years.…”
Section: Introductionmentioning
confidence: 99%